The thing in-itself and its role in the constitution of objectivity. A critical reading of Onof´s reconstruction of transcendental affection - Beade, Ileana Paola (2013)
In this paper, I shall consider some conclusions drawn by Christian Onof in a recent paper, in which the author analyzes the problem of transcendental affection. Onof assumes that Kant´s references to the thing-in-itself as the cause (or ground) of sensible affection require some sort of justification, for -as he claims- these references are grounded in a metaphysical assumption, that is: the existence of something real beyond the subject`s mind. I will suggest, on the contrary, that Kant´s confidence in the existence of a non-subjective reality should not be characterized a metaphysical assumption, and would not require, therefore, any particular justification. The other main issue I will consider concerns the position adopted by Onof in relation to the current debate between the so called two-objects interpretation and the two-aspects interpretation (concerning the critical distinction between appearances and things-in-themselves). Although Onof attempts to go beyond this dichotomy, I will try to show that many of his statements about the thing-in-itself and affection are not incompatible with some conclusions drawn in the frame of the two-aspects interpretation (or epistemic interpretation), which Onof, however, explicitly rejects.